2019
DOI: 10.1021/acs.jafc.9b01265
|View full text |Cite
|
Sign up to set email alerts
|

First Anti-ToCV Activity Evaluation of Glucopyranoside Derivatives Containing a Dithioacetal Moiety through a Novel ToCVCP-Oriented Screening Method

Abstract: Tomato chlorosis virus (ToCV) is a newly reported plant virus that has rapidly spread to all parts of the world, resulting in a serious decline in tomato quality and yield due to the lack of effective control agents. In this study, the ToCV coat protein (ToCVCP) was expressed and purified in Escherichia coli, and a series of novel glucopyranoside derivatives containing a dithioacetal moiety was designed and synthesized. The binding affinity of these compounds to ToCVCP was determined using microscale thermopho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 22 publications
(39 reference statements)
3
32
0
Order By: Relevance
“…The desalted ToCVCP was determined by 12% SDS-PAGE, and the results are presented in Figure A. An obvious band was observed in lane 1 at the 30 K d position and was the same location based on previous reports …”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…The desalted ToCVCP was determined by 12% SDS-PAGE, and the results are presented in Figure A. An obvious band was observed in lane 1 at the 30 K d position and was the same location based on previous reports …”
Section: Resultssupporting
confidence: 63%
“…All samples were tested by using the polymerase chain reaction (PCR). The primer sequence used in the PCR was based on means reported by our research group as before . After N.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, harpin binding protein-1 is a potential target activated antiviral response in tobacco by antiviral agent dufulin [ 81 ], and tomato chlorosis virus (ToCV), CP play significant roles in sustaining the methyl cycle and S-adenosylmethionine-dependent methyltransferase activity and its minor CP play important roles in silencing suppression activity to counteract the RNA silencing-mediated defense response of the host [ 82 , 83 ]. Glucopyranoside derivatives, pyrimidine derivatives, 4(3H)-quinazolinone derivatives, and novel quinazolinone sulfide inhibitors targets ToCV coat protein with high anti-ToCV activity [ 84 , 85 , 86 , 87 ], and its minor coat protein is regarded as a novel target for the new green anti-ToCV inhibitors [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bioassays demonstrated that compound 113 (Figure 35) had excellent anti-TMV activities, and its curative, protection, and inactivation activities for TMV were 50.9%, 58.9%, and 81.8%, respectively, which were clearly superior to those of Ribavirin. Xie et al [116] designed and synthesized two series of novel glucopyranoside derivatives containing a dithioacetal moiety. Results revealed that compounds 114 and 115 (Figure 35) interacted with ToCV-CP with K d values of 0.12 and 0.21 μM, respectively, meanwhile quantitative reverse transcription polymerase chain reaction (qRT-PCR) was used to evaluate the anti-ToCV activity of compounds 114 and 115 in vivo, and qRT-PCR results showed that compounds 114 and 115 could significantly reduce the expression level of ToCV-CP gene in tomato compared with Ningnanmycin.…”
Section: Antiviral Activitymentioning
confidence: 99%